Influência da adição do NaCl e KCl em sistemas de pastas contendo sílica para poços de petróleo em zonas evaporíticas e carbonáticas - Barbosa, Carina Gabriela de Melo e Melo (2012)
One of the major challenges faced nowadays by oil companies is the exploration of pre-salt basins. Thick salt layers were formed in remote ages as a consequence of the evaporation of sea water containing high concentrations of NaCl and KCl. Deep reservoirs can be found below salt formations that prevent the outflow of oil, thus improving the success in oil prospection. The slurries used in the cement operations of salt layers must be adequate to the properties of those specific formations. At the same time, their resulting properties are highly affected by the contamination of salt in the fresh state. It is t herefore important to address the effects of the presence of salt in the cement slurries in order to assure that the well sheath is able to fulfill its main role to provide zonal isolation and mechanical stability. In this scenario, the objective of the present thesis work was to evaluate the effect of the presence of NaCl and KCl premixed with cement and 40% silica flour on the behavior of cement slurries. Their effect in the presence of CO2 was also investigated. The rheological behavior of slurries containing NaCl and KCl was evaluated along with their mechanical strength. Thermal and microstructural tests were also carried out. The results revealed that the presence of NaCl and KCl affected the pozzolanic activity of silica flour, reducing the strength of the hardened slurries containing salt. Friedel´s salt was formed as a result of the bonding between free Cl- and tricalcium aluminate. The presence of CO2 also contributed to the degradation of the slurries as a result of a process of carbonation/bicarbonataion